Design and Fabrication of Improved Socket System, the Triple-Side Wall Expansion Socket System for Better Comfort of Transtibial Amputees - Sahil Rasiklal Patel; Gouri Mahato (Journal of Integrated Health Sciences)
Background: Transtibial prosthesis is a device specifically replaces the part of the leg that is below the knee joint. Mostly the amputees are dependent on others and live a sedentary life when they cannot function effectively and efficiently with their prosthesis.[1] To wear a prosthesis whole day long requires better comfort as well as the function along with the other components. The prosthetic socket is the main connector between the residual and prosthesis. Poor socket fitting directly affects socket comfort, function, and workability of the user, making them more dependent and psychologically depressed and weaker and creating challenges for the user, family, and rehabilitation professionals.[2] Aims and Objective of the Study: The purpose of the research work is to design and fabricate a comfortable socket design which can be fitted to provide better comfort to the users. Methodology: The study is based on custom-made socket where modification needs to be done on the socket part and in the fabrication procedure. Results: During fitment, 70% of users found it significantly comfortable and improved in ambulation. Conclusions: For the triple-side wall expansion socket system, it can be concluded that change in socket for better function is also could be an alternative for troublesome residual limb amputees.